EFFECTIVENESS OF GROUP GUIDANCE SERVICES IN MINIMIZING SMARTPHONE ADDICTION - Winarni, Ita (Faculty of Tarbiyah nad Teacher Training, 2023)
Smartphone addiction is a problem among students in the technology era. In this context, guidance from adults (teachers or parents) is needed for children (students). This study aims to determine the effectiveness of group guidance services in minimizing smartphone addiction. The background of this research is at SDN 101910 Sidodadi, specifically the research subjects, namely 30 students of class VI for the academic year 2022/2023 to test how big the level of smartphone addiction is among students, between before and after being given group guidance services. The type of this research is counseling guidance action research (PTBK), carried out in 2 cycles. Data analysis was carried out quantitatively using questionnaires and observations. The results of this study indicate the level of smartphone addiction of VI SDN 101910 Sidodadi students when a pre-test was held on 8 students (26.7%), 2 students in the high category, and 6 students in the very high category. Furthermore, in the first cycle, group guidance services were provided through group discussions, lectures, questions and answers, and filling out questionnaires. There were 2 students (6.7%) who were still addicted to smartphones in the high category and 4 students in the medium category, 2 students in the low category. In cycle II, 1 student (3.3%) was still addicted to smartphones in the high category, 3 students in the low category, and 4 students in the very low category. Thus, it was concluded that the level of smartphone addiction in students decreased after being given counseling services.